Dialogue of Generations as Communicative Dimension of Bread Culture Semantics in the Ukrainian Sacral Tradition - Khrypko, Svitlana Anatolievna (Journal of History Culture and Art Research, 2020)
The issue is devoted to the semantic analysis of the bread phenomenon in Ukrainian cultural tradition. The traditional interrelations between a man and bread are considered. The layers of taboos, prohibitions about common bread usage are presented. According to Ukrainian spiritual tradition, bread was a vital symbol, it was worshipped as the Sun in the pagan times and as the Eternal Sun of Truth in the Christian times. Consequently, it is forbidden to swear, deal about dishonest affairs, mention evil spirits (in all sounding variants), have empty talks and to be occupied by a charade, etc. in the presence of “sacred bread”. The Christian layer of bread consideration as Jesus Christ embodiment is highlighted. The sinful context of bread usage is provided. The greatest sin was to offense a Mother, Earth, and Sacred Bread, and consequently to be separated from a family (without a family blessing), to lose a piece of land (without an opportunity to confess, as people confessed to sacred land the in old times), and also without any possibility to grow wheat personally (in other words to be deprived by God’s protection). The folk wisdom has always mentioned that: “A family table is the palms of God. A loaf of bread on a table is God’s Gift. The attitude to this gift should be respectful”. The main paradigm of the whole issue claims the following thesis: bread’s magic has gone through all Ukrainian spiritual culture, all sacral and mystical ritual nuances, whole mystery sense of Ukrainian folk laws are presented. The exclusiveness of various bread names is considered, hence the names are provided owing to bread’s shapes, special holidays’ application, specific of bread-making process, etc. The crucial attention is paid to Christmas bread and variants of its production.